Husbandry and traditional practices in field flocks of Madras Red sheep - R Venkataramanan; V Arthy; C Sreekumar; G Manonnmani; H Gopi (Journal of Livestock Biodiversity, 2025)
A survey was conducted on the husbandry and traditional practices followed in 107 Madras Red sheep flocks belonging to beneficiaries of ICAR-Network Project on Sheep Improvement-Madras Red field unit (NWPSI). The flocks were maintained under extensive system of management, with flock size ranging from 25 to 180 and majority having between 30-60 breeding females. More than half of the farmers surveyed (52.4%) housed their flocks in thatched sheds, while the remaining left their animals in open areas fenced with chain-link or thorny bushes. Several farmers (68.2%) owned agricultural land. Natural mating was the norm, with an average sex ratio (ram/ewe) of 1 ram per 38 ewes (2.64%). Identification of animals was practised in some flocks using paint or ear notching. Aged ewes were usually disposed by selling to the butcher, with very few farmers maintaining them until death. The main source of income was from sale of ram lambs through middlemen. In addition to sheep, farmers also reared other livestock such as goats, buffaloes, cows and poultry species or a combination of these. The water sources for the animals were lakes, bore wells, ponds and wells. None of the farmers maintained records, insured their animals or cultivated fodder. Traditional treatment practices were followed by the majority of the farmers. Scientific management practices were followed by all the farmers as the inputs were provided by the NWPSI. Superstitious beliefs still exists among the farmers. Shrinking of grazing area, disease, predation by feral dogs and safety for the women grazers were some of the problems encountered.